Infotainment jako narzędzie formatowania społeczeństwa w warunkach medialnej demokracji - Golinowski, Janusz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
As the mass media spread a defined format of ‘cultural repertoires’, they operate both in the cognitive and affective realms – they present problems and issues to society (societies), they form public opinion and stimulate actors to undertake actions. These result in both actual and symbolic unification of individuals and groups on various levels of the organization of community life. Even after a superficial observation of present activities it can be assumed that the process of marketization of social life, which includes the realm of culture and human relations, has been subjected to the influence of a populist rhetoric, which is rooted in the therapeutic function mass culture performs, formatting and unifying citizens’ behavior. The reasons for this can be sought in the tendency, which is typical both of economic and political marketing, to make promises and refer to unconditioned human desires. Overfamiliarity and excessive expression can play the same role in persuading viewers to accept the ‘only right opinion’, as can the propaganda of a given political platform under authoritarian conditions. In these terms the normative approach to the realm of politics and the politicization of social life reveal their anachronistic nature in defining real decision processes.